Cloning and expression of ricin a- and b-subunits genes in fusion constructions with dihydrofolate reductase gene in escheriсhia coli. - M. А. Gracheva; Z. М. Galushkina; N. N. Poletaeva; L. V. Verhovskaya; V. G. Lunin; V. I. Shvets (Тонкие химические технологии)
Recombinant chimeric constructions RTA-DHFR and RTВ-DHFR consisting of ricin Aand B-subunits genes (RTA and RTB) and dihydrofolate reductase (DHFR) gene were cloned and expressed in Escheriсhia coli. Antigenic properties of RTA and RTB retained in chimeric proteins RTA-DHFR and RTВ-DHFR.